N-(3-Fluorobenzoyl)-N′,N′′-bis(4-methylphenyl)phosphoric triamide - Pourayoubi, Mehrdad (International Union of Crystallography, 2011)
In the title compound, C(21)H(21)FN(3)O(2)P, the NH and P(=O) groups of the C(=O)NHP(=O) fragment are in a syn arrangement with respect to each other, as are the two amide H atoms of the two CH(3)–4-C(6)H(4)–NH moieties. In the crystal, molecules are linked through N—H⋯O(=P) and N—H⋯O(=C) hydrogen bonds, forming R (2) (2)(8) and R (2) (2)(12) rings, which are arranged in chains parallel to [010].